Superficial CD34 Positive Fibroblastic Tumor: A rare mesenchymal tumor of borderline malignant potential. (Journal of Pathology of Nepal, 2024)
Superficial CD34 positive fibroblastic tumor is a rare soft tissue tumor first brought to light by Jodi M Carter in 2014. Several cases have been reported since, and they have been newly included in the recent WHO classification under the fibroblastic and myofibroblastic tumors category. It is a mesenchymal neoplasm of borderline malignant potential predominantly found in middle-aged adults with a median age of 37 years and most commonly located in the lower extremities. It is a spindle cell tumor with pleomorphic epithelioid cells, low mitotic activity, and strong diffuse positivity for CD34 on immunohistochemistry. The prognosis is good post excision but needs long-term follow-up since few cases revealed recurrences and lymph node metastases. As far as we know, only 64 cases have been documented thus far. We have reported a 63-year female with essential histological features of superficial CD34 positive fibroblastic tumor with no local recurrence or metastasis to date.